DESIGN OF EMPLOYEE DATA ELECTRONIC ARCHIVES FOR VEHICLE MAINTENANCE BASED ON MICROSOFT EXCEL AT HR DEPARTMENT IN PT BETON ELEMENINDO PERKASA BATUJAJAR) - Ega Yohana Zeami; Yayan Firmansyah; Tangguh Dwi Pramono (Records Management System Journal, 2022)
Electronic archive management has become a demand and need for every organization in the era of digital technology as it is today. Electronic records management is closely related to the use of computer technology, which can complete records management work more effectively and efficiently. The archive system in the HR Department at PT Beton Elementindo Perkasa, especially for employee archives, still uses the manual archiving method, this causes the recovery of archives to take quite a long time and there are some lost files. With the design of this archival system, it is hoped that some of the problems caused by the previous archival system can be resolved properly. The change from manual filing system to electronic filing system begins with analyzing data needs, tools and several other support systems, then continues with column creation and data input in Microsoft Excel and the last process is scanning documents as additional backup for this employee archive. After a direct trial, it is proven that with this archive system, the recovery of archives can be faster and the risk of loss of information due to damaged archives can be minimized. The result of this work is inform of a the file in the form of Microsoft Excel in which there is information about the personal data of employees of thesection vehicle maintenance which is equipped with a hyperlink to insert file attachments and passwords to access the data in it which aims to maintain the confidentiality of the data in it so that it is not misused. by the responsible party. It is hoped that this electronic filing system can be further developed in the future to facilitate and expedite the work in the HR Department at PT Beton Elementindo Perkasa.